MAIT cells are depleted early but retain functional cytokine expression in HIV infection. Issue 2 (28th October 2014) - Fernandez, Caroline S; Amarasena, Thakshila; Kelleher, Anthony D; Rossjohn, Jamie; McCluskey, James; Godfrey, Dale I; Kent, Stephen J
Abstract : Mucosal‐associated invariant T (MAIT) cells home to mucosal sites and exert antimicrobial activity against bacteria and other microorganisms. HIV infection leads to early depletion of gut T cells and translocation of bacterial products. There are reports that MAIT cells, defined by coexpression of Vα7.2 and CD161, are depleted during HIV infection and residual MAIT cells are functionally impaired. However, one study suggested that MAIT cells might remain after HIV infection but evade detection through CD161 downregulation. Thus, the impact of HIV infection on MAIT cells is unclear. We studied longitudinal blood samples from 31 HIV‐infected subjects for MAIT cell numbers, phenotype and function using both standard Vα7.2/CD161 surface markers and an MR1 tetramer. We found that MAIT cells were depleted early during HIV infection, and although there was a concomitant rise in Vα7.2 + CD161 – cells, these were MR1 tetramer negative, indicating that these are unlikely to be altered MAIT cells. Antigen‐mediated activation of residual MAIT cells showed that they remained functional out to 2 years following HIV infection. Although MAIT cells are depleted in HIV infection, residual and functionally active MAIT cells persist and may still be able to assist in controlling bacterial translocation during HIV infection.